Pengaruh Current Ratio, Debt To Assets Ratio Dan Profit Margin Terhadap Laba Bersih PT. Selamat Sempurna Tbk. Di Bursa Efek Indonesia - Wawan Hermanto; Mahmudin S (E-Journal Studia Manajemen, 2015)
This study aims to determine the effect of the current ratio, debt to assets ratio and profit margin on net income with descriptive quantitative research methods. The subject of this research is PT. Congratulations Perfect Tbk using secondary data from financial reports in the Indonesian Stock Exchange (BEI) in the year 2009-2013. Data were analyzed using (1) Analysis of multiple regression, (2) test classic assumptions; Test multicollinearity, heteroscedasticity, normality and autocorrelation (3) Correlation analysis, (4) The coefficient of determination, (5) test hypotheses, and (6) Test F. The results membutktikan that simultaneous current ratio, debt to assets ratio and profit margin no effect on net income.